MATHEMATICS, ART AND TECHNOLOGY: INTERDISCIPLINARITY, COMPLEMENTATION AND COOPERATION - Marques Junior, E.; Marques, E. M. R. [UNESP]; Souza, A. R. [UNESP]; Chova, L. G.; Martinez, A. L.; Torres, I. C. (Iated-int Assoc Technology Education & Development, 2018)
We developed this Project with the aim to arouse interest in high school students and the general public for the area of Mathematics, motivated by the great social demand for improving the quality of teaching in this area. We believe that greater student interest and the ability to understand complex number applications in various areas, cooperates with the teaching/learning process. Thus we intended to develop the content of complex numbers and their elementary functions associated with Art and Technology. For this, we propose interrelated activities: itinerant expositions of pictures created with computer graphics from complex functions; explanatory lectures on the software and the process of creation of the charts (Method of the Colored Domains), workshops in computer labs for production by the students of High School participating in the project, production of material for study and development of this mathematical content and production of new pictures; preparation of dissemination material and repository of knowledge generated in the project (e-books, articles); use of e-learning technology (Hangout, Moodle, etc.) in the preparation and development of activities for teachers and students of High School; among others. We also aimed at the dissemination of part of the scientific production of the Research Group Teaching of Sciences and Educational Technology of the Faculty of Sciences of UNESP - campus of Bauru, which has been working on the subject for several years, having produced the software that enables creation of the proposed Pictures in the development of the project. On the Matematica e Arte website, available at http://www2.fc.unesp.br/matematicaearte/download.php, publications on the subject are available, pictures already produced and the educational software F(C): Complex Functions for free download. The site also has a brief history of the research project, teaching and extension and contact addresses with the project coordination.
Keywords: complex numbers; computer graphics; geometric and aesthetic regularities